FAKTOR FAKTOR YANG MEMPENGARUHI KUALITAS INFORMASI LAPORAN KEUANGAN PEMERINTAH DAERAH - Siti Qomah (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2021)
This research was conducted to recognize the implementation of the implementation of government accounting standards, internal control systems, human resource competence, and information utilization of information on the quality of local government financial statements. Quantitative is used for approaches in this study. In the Financial Agency of Boyolali Regency of the election of the research for research. With the amount of 63 employees used as samples. Sampling with purposive sampling. Data collection with the spread of questionnaire. The method of data analysis used is multiple linier regression analysis. The results of this study prove that the effect of the implementing government accounting standards and internal control system have an effect on the qualityof local government financial reports, otherwise competence of human resources and information technology utilization does not affect the quality of local government financial statement.